The Increase in Hospitalizations for Urinary Tract Infections and the Associated Costs in the United States, 1998–2011. (24th February 2017) - Simmering, Jacob E.; Tang, Fan; Cavanaugh, Joseph E.; Polgreen, Linnea A.; Polgreen, Philip M.
Abstract: Background: Outpatient therapies for urinary tract infections (UTIs) are becoming limited due to antimicrobial resistance. The purpose of this paper is to report how the incidence of hospitalizations for UTIs have varied over time in both men and women and across age groups. We also explore how the severity for UTI hospitalizations has changed and describe the seasonality of UTI hospitalizations. Methods: Using the Nationwide Inpatient Sample, we compute a time-series of UTI incidence and subdivide the series by age and sex. We fit a collection of time-series models to explore how the trend and seasonal intensity varies by age and sex. We modeled changes in severity using regression with available confounders. Results: In 2011, there were approximately 400000 hospitalizations for UTIs with an estimated cost of $2.8 billion. Incidence increased by 52% between 1998 and 2011. The rate of increase was larger among both women and older patients. We found that the seasonal intensity (summer peaks and winter troughs) increased over time among women while decreasing among men. For both men and women, seasonality decreased with advancing age. Relative to controls and adjusted for demographics, we found that costs among UTI patients grew more slowly, patients left the hospital earlier, and patients had lower odds of death. Conclusions: Incidence of UTI hospitalization is increasing and is seasonal, peaking in the summer. However, the severity of UTI admissions seems to be decreasing, indicating that patients previously treated as outpatients may now be admitted to the hospital due to increasing antimicrobial resistance.